2023
DOI: 10.1037/dev0001581
|View full text |Cite
|
Sign up to set email alerts
|

Tracking informal fraction knowledge and its correlates across first grade.

Abstract: Young children have informal knowledge of fractions before learning about fraction symbols in school. In the current study, we followed 103 children in the Mid-Atlantic United States from the fall to the spring of first grade to characterize the development of individual differences in early informal fraction knowledge, as well as its relation to other mathematical and cognitive skills. Most children in our sample showed some early fraction knowledge at the beginning of first grade, especially with nonsymbolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Throughout their lives, AEP-1 students also accumulated experiences with whole numbers in formal and informal contexts, which may support their performance in fraction tasks and limit the quantity and type of errors they make. Previous studies have shown that students' whole number knowledge predicts their performance in fraction tasks (e.g., Sidney & Alibali, 2017;Viegut et al, 2023). Future studies should investigate how whole number skills predict fraction skills in AEP-1 students, to identify pedagogical approaches that may support this particular group.…”
Section: Effects Of Informal Experiences On Fraction Knowledgementioning
confidence: 97%
See 3 more Smart Citations
“…Throughout their lives, AEP-1 students also accumulated experiences with whole numbers in formal and informal contexts, which may support their performance in fraction tasks and limit the quantity and type of errors they make. Previous studies have shown that students' whole number knowledge predicts their performance in fraction tasks (e.g., Sidney & Alibali, 2017;Viegut et al, 2023). Future studies should investigate how whole number skills predict fraction skills in AEP-1 students, to identify pedagogical approaches that may support this particular group.…”
Section: Effects Of Informal Experiences On Fraction Knowledgementioning
confidence: 97%
“…Both studies found that children read and write fractions as whole numbers, justifying our hypotheses. Finally, we predicted that informal numerical experiences (e.g., outside the school setting) may be associated with fraction writing skills based on previous studies on whole-number knowledge, which have shown that informal mathematics experience contribute to formal mathematics skills in general (e.g., Benavides-Varela et al, 2023;LeFevre et al, 2009;Levine et al, 2011;Napoli & Purpura, 2018;Ramani et al, 2015;Siegler & Ramani, 2009), and fraction skills, specifically (Viegut et al, 2023).…”
Section: Present Studymentioning
confidence: 99%
See 2 more Smart Citations